The nematicidal potential of novel fungus, Trichoderma asperellum FbMi6 against Meloidogyne incognita - Ritul Saharan; J. A. Patil; Saroj Yadav; Anil Kumar; Vinod Goyal (Scientific Reports, 2023)
Abstract One of the most damaging pests in vegetable crops is the root-knot nematode (Meloidogyne incognita) worldwide. The continuous use of nematicide is costly and has unintended consequences for human and environmental health. To minimize nematicides, eco-friendly integrated nematode management is required. Trichoderma, an antagonistic fungus has been explored to control root-knot nematode. The fungal bio-control strain FbMi6 was identified as Trichoderma asperellum (accession no. MT529846.1). T. asperellum FbMi6 showed substantial nematicidal activity in the laboratory, with egg hatch suppression (96.6%) and juvenile mortality (90.3%) of M. incognita. T. asperellum FbMi6 was examined under pot and field  conditions (after neem cake enrichment), both alone and in combination, and compared with controls. Application of T. asperellum FbMi6 enriched neem cake (1-ton ha-1) increased (28.3%) the okra yield and decreased (57.1%) nematode population as compared with control. T. asperellum FbMi6 enriched neem cake had higher polyphenol content (resistance enhancer) in okra compared with inoculated check.